Numerical simulation and dynamical response of a moored hydrokinetic turbine operating in the wake of an upstream turbine for control design. (December 2017) - Pyakurel, Parakram; VanZwieten, James H.; Sultan, Cornel; Dhanak, Manhar; Xiros, Nikolaos I.
Abstract: Numerical simulation of a downstream hydrokinetic turbine operating in the wake of an upstream turbine for feedback control design is presented. Wake effects from an upstream turbine are quantified in terms of wake velocity and amplified turbulence levels. These effects are integrated in an in-stream hydrokinetic turbine numerical simulation that utilizes a Blade Element Momentum approach with a dynamic wake inflow model. Simulations are carried out on a fixed turbine model to simulate operation in river or tidal channels with conventional foundations, as well as on a compliantly moored turbine model such as those designed to operate in open ocean currents. Highlights: Algorithms to calculate wake velocity and turbulence intensity behind an in-stream hydrokinetic turbine are presented. The presented algorithms are integrated into a turbine simulation that utilizes unsteady Blade Element Momentum method. Performance of downstream turbine in the wake of upstream turbine is presented. Hydrodynamic parameters are calculated and motion analysis of moored turbine is presented.